Species traits explain public perceptions of human–bird interactions. Issue 8 (14th July 2022) - Andrade, Riley; Larson, Kelli L.; Franklin, Janet; Lerman, Susannah B.; Bateman, Heather L.; Warren, Paige S.
Abstract: The impacts of urbanization on bird biodiversity depend on human–environment interactions that drive land management. Although a commonly studied group, less attention has been given to public perceptions of birds close to home, which can capture people's direct, everyday experiences with urban biodiversity. Here, we used ecological and social survey data collected in the metropolitan region of Phoenix, Arizona, USA, to determine how species traits are related to people's perceptions of local bird communities. We used a trait‐based approach to classify birds by attributes that may influence human–bird interactions, including color, size, foraging strata, diet, song, and cultural niche space based on popularity and geographic specificity. Our classification scheme using hierarchical clustering identified four trait categories, labeled as Metropolitan (gray, loud, seedeaters foraging low to ground), Familiar (yellow/brown generalist species commonly present in suburban areas), Distinctive (species with distinguishing appearance and song), and Hummingbird (hummingbird species, small and colorful). Strongly held beliefs about positive or negative traits were also more consistent than ambivalent ones. The belief that birds were colorful and unique to the regional desert environment was particularly important in fortifying perceptions. People largely perceived hummingbird species and birds with distinctive traits positively. Similarly, urban‐dwelling birds from the metropolitan trait group were related to negative perceptions, probably due to human–wildlife conflict. Differences arose across sociodemographics (including income, age, education, and Hispanic/Latinx identity), but explained a relatively low amount of variation in perceptions compared with the bird traits present in the neighborhood. Our results highlight how distinctive aesthetics, especially color and song, as well as traits related to foraging and diet drive perceptions. Increasing people's direct experiences with iconic species tied to the region and species with distinguishing attributes has the potential to improve public perceptions and strengthen support for broader conservation initiatives in and beyond urban ecosystems.